4‐phenylbutyric acid—Identity crisis; can it act as a translation inhibitor?. Issue 12 (14th November 2022) - Stein, Daniel; Slobodnik, Zeev; Tam, Benjamin; Einav, Monica; Akabayov, Barak; Berstein, Shimon; Toiber, Debra
Abstract: Loss of proteostasis can occur due to mutations, the formation of aggregates, or general deficiency in the correct translation and folding of proteins. These phenomena are commonly observed in pathologies, but most significantly, loss of proteostasis characterizes aging. This loss leads to the chronic activation of stress responses and has a generally deleterious impact on the organism. While finding molecules that can alleviate these symptoms is an important step toward solutions for these conditions, some molecules might be mischaracterized on the way. 4‐phenylbutyric acid (4PBA) is known for its role as a chemical chaperone that helps alleviate endoplasmic reticulum (ER) stress, yet a scan of the literature reveals that no biochemical or molecular experiments have shown any protein refolding capacity. Here, we show that 4PBA is a conserved weak inhibitor of mRNA translation, both in vitro and in cellular systems, and furthermore—it does not promote protein folding nor prevents aggregation. 4PBA possibly alleviates proteostatic or ER stress by inhibiting protein synthesis, allowing the cells to cope with misfolded proteins by reducing the protein load. Better understanding of 4PBA biochemical mechanisms will improve its usage in basic science and as a drug in different pathologies, also opening new venues for the treatment of different diseases. Abstract : 4PBA is a weak inhibitor of mRNA translation, and it does not directly promote protein folding nor prevents aggregation. Instead, it possibly alleviates proteostatic or ER stress by inhibiting protein synthesis, allowing the cells to cope with misfolded proteins by reducing protein load. Such a mechanism of function is already found in the cell—in the ER stress alleviation through eIF2a phosphorylation.